Roland Barthes Semiotics Analysis of Human Interest Works at The Beauty Of Photography Exhibition - Herry, Herry; Enrieco, Edward; Lukman , Lukman; Paksi, Yudha Febri Al (Marqcha Institute, 2024)
This research is titled Roland Barthes Semiotics Analysis of Human Interest Work at The Beauty of Photography Photo Exhibition. The purpose of this study is to determine the influence of human interest aspects on photojournalism at The Beauty of Photography photo exhibition. In selecting photo objects for the collection of respondents taken from photos by students as photo exhibition participants at the time of the photo exhibition. The theory used and considered relevant in this research is Roland Barthes Theory. The method used in this research uses a descriptive qualitative interpretive study method with a critical paradigm. This study found that the meaning of connotation is found in the photos analyzed and that the results of the photos can be understood not only by looking at the photos, but there are ways of reading certain photos so that the message received is in accordance with what the photographer wants to convey.